Entrepreneurial management and technology-based firm performance - Abdul Majid, Izaidin; Cooper, Sarah; Levie, Jonathan; Ismail, Kamariah (Penerbit Universiti Teknikal Malaysia Melaka, 2007)
This research explores the relationship between entrepreneurial management (EM)and the performance or growth of firms in the Multimedia Super Corridor ofMalaysia. A common opinion and assumption shared among many scholars onthis subject is that there is a positive relationship between entrepreneurialbehaviours and organizational profitability. In other words they believe thatentrepreneurially-managed firms tend to register higher performance and growth.This research adopts Stevenson's (1983) approach on entrepreneurialmanagement, which was developed, and operationalised thoroughly by Brown etal. (2001). Included in the Stevenson's six dimensional construct of EM which wasconsidered as firm-level measurement of entrepreneurial inclination of the firm asoperationalised by Brown et al. (2001) are Strategic Orientation; ResourceOrientation; Management Structure; Reward Philosophy; Growth Orientation; andEntrepreneurial Culture. The results reveal that EM to some extent does contributesignificantly and positively to firms' performance. The results also indicate thatthree dimensions of EM approach namely Growth Orientation, StrategicOrientation and Management Structure were the best predictors of firmperformance.